2020
DOI: 10.21203/rs.2.20462/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identification and analysis of CYP450 supergene family members from the transcriptome of Aralia elata (Miq.) Seem reveal candidate genes for triterpenoid saponin biosynthesis

Abstract: Background: Members of the cytochrome P450 (CYP450) gene superfamily have been shown to play essential roles in regulating secondary metabolites biosynthesis. However, the systematic identification and bioinformatics analysis of CYP450s have not been reported in Aralia elata (Miq.) Seem , a highly valued medicinal plant. Results: In the present study we conducted the RNA-sequencing (RNA-seq) analysis of the leaves, stems, and roots of A. elata, yielding 66,713 total unigenes. Following the annotation and class… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…We found that homologs of CSE were upregulated by 1.34- and 1.23-fold time, respectively. In addition, eight genes encoding cytochrome P450 (CYP450) and seven genes encoding UDP-glycosyltransferase (UGT) related to the biosynthesis of triterpene saponins ( Cheng et al, 2020 ), were higher upregulated by strain Pl7 treatment. These results indicated that B. halotolerans strain Pl7 can induce apple defenses primarily via regulating the secondary metabolite biosynthesis pathways.…”
Section: Discussionmentioning
confidence: 99%
“…We found that homologs of CSE were upregulated by 1.34- and 1.23-fold time, respectively. In addition, eight genes encoding cytochrome P450 (CYP450) and seven genes encoding UDP-glycosyltransferase (UGT) related to the biosynthesis of triterpene saponins ( Cheng et al, 2020 ), were higher upregulated by strain Pl7 treatment. These results indicated that B. halotolerans strain Pl7 can induce apple defenses primarily via regulating the secondary metabolite biosynthesis pathways.…”
Section: Discussionmentioning
confidence: 99%
“…In A. elata , genes that potentially encode these key enzymes, including AeFPS ( Wu, 2011 ), AeSS ( Cheng, 2011 ), AeSE ( Zhao, 2012 ), and β-AeAS ( Wu, 2011 ) have been cloned and investigated by real-time qRT-PCR. In addition, 254 members of P450 and 122 UGT families were identified by the RNA-sequencing analysis ( Cheng et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%